Δ18O Analyses of the Humpbacked Conch (Gibberulus gibberulus): Evaluating a Proxy for Reconstructing Sea-Surface Temperature at Chelechol ra Orrak, Palau. (2nd October 2018) - Dodrill, Taylor N.; Jew, Nicholas P.; Fitzpatrick, Scott M.
ABSTRACT: In Palau, Micronesia, marine resources, particularly shellfish, played a vital role in human subsistence for millennia. Despite the vast array of molluscan species in archaeological assemblages, there is a dearth of data on nearshore palaeoecology or prehistoric shellfish foraging practices. In this study, we analysed stable oxygen isotopes ( δ 18 O) values present in the calcium carbonate shell of Gibberulus gibberulus from the Chelechol ra Orrak archaeological site to reconstruct average nearshore sea-surface temperatures (SST) from approximately 1500–1100 cal BP. Modern shellfish samples and environmental data were collected from intertidal zones near the site and x-ray diffraction (XRD) was employed to identify the biomineralogical composition of G. gibberulus . These steps provide necessary information for the selection of the proper oxygen isotope-to-SST conversion formula. The selected formula was applied to δ 18 O samples from archaeological shells to reconstruct prehistoric SST averages. The results of this proxy validation study verify that G. gibberulus accurately records ambient SST and can be used to reconstruct ancient nearshore conditions. These findings also contribute to the establishment of an environmental baseline, which can be used to examine how environmental changes may have influenced the availability of molluscan taxa that in turn influenced human subsistence practices through time.